Does P2P Lending Have an Impact on Regional Economic Growth? Evidence from Java Provinces - Amrillah, Miftah Khairi; Felianty, Telisa Aulia (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
It is generally admitted that a relationship exists between financial system development and economic growth, although the nexus between these two is complex. Due to the advancement of technology, P2P lending has become a growing industry in Indonesia as an alternative credit different from a conventional bank, which also might contribute to fostering economic growth. This paper's purpose is to analyze the contribution of P2P lending to Product Domestic Regional Bruto (PDRB) in 5 provinces in Java, which are Banten, DKI Jakarta, West Java, Central Java, DI Yogyakarta, and East Java, using fixed effect panel regressions from Q1-2020 to Q2-2022 period. This paper finds a significant and positive impact of P2P lending on real PDRB growth, with a 0,0754% magnitude. Although there is a positive impact, many challenges still need to be overcome in the P2P lending industry.